2016
DOI: 10.1159/000441767
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Severity Predicts Long-Term Prognosis in Crohn's Disease Patients with Clinical Remission

Abstract: Introduction: Mucosal healing has emerged as a desirable treatment goal in clinical practice for patients with Crohn's disease (CD). The aim of this study was to assess the relationship between endoscopic activity and the long-term prognosis of CD using simple endoscopic score for Crohn's disease (SESCD) and Rutgeerts' score. Methods: We conducted a cohort study in clinical practice at a single center. Among CD patients who underwent colonoscopy between July 2008 and June 2011 at our hospital, 131 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…As for the 37% of IBD patients not having had any diagnostic and/or follow-up procedures in the year before IBD-related hospitalization, this number compares well with the 43% of patients not being treated with IBD-specific drugs. It is crucial to remember that IBD patients need regular follow-up visits even if they are asymptomatic as also patients in clinical remission might have ongoing endoscopically active disease that is associated with bowel damage in the long term [22,[24][25][26]. We observed that IBD patients who were followed by gastroenterologists received more frequently IBD drug treatment (5-ASA, steroids, immunomodulators, and biologics) when compared with patients who were followed by primary care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…As for the 37% of IBD patients not having had any diagnostic and/or follow-up procedures in the year before IBD-related hospitalization, this number compares well with the 43% of patients not being treated with IBD-specific drugs. It is crucial to remember that IBD patients need regular follow-up visits even if they are asymptomatic as also patients in clinical remission might have ongoing endoscopically active disease that is associated with bowel damage in the long term [22,[24][25][26]. We observed that IBD patients who were followed by gastroenterologists received more frequently IBD drug treatment (5-ASA, steroids, immunomodulators, and biologics) when compared with patients who were followed by primary care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent paediatric anti-TNF cohort study with planned follow up endoscopy between 9-12 months also reported positive predictive value of complete MH with 79% clinical remission rates at 2 years in those with achieving complete MH vs. 67% with partial MH (SES-CD drop>50%) (195). Complete disappearance of ulcers (CDEIS=0) or a tighter definition of endoscopic healing (SES-CD £2) can lead to superior outcomes, this concurs with our findings as only those with complete MH had good outcomes (245)(246) Our early mucosal healing rates following EEN therapy are comparable (33%) to our previous reports of 44%. (175) Our study is also the first to prospectively examine the impact of early EEN induced mucosal healing on important real-life long term clinical outcomes i.e need for Infliximab/CS or surgical resection in a well characterised cohort with a consistent practice of diagnosing and management of CD relapse.…”
Section: Discussionsupporting
confidence: 88%
“…Using combination of biomarkers targets to make treatment adjustments can lead to better outcomes as demonstrated by the recent CALM study. Aiming for CRP<5 mg/L and FC <250 micogram/gm strongly correlated with endoscopic remission (246).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation